2023
DOI: 10.1155/2023/9808556
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle Incorporated Human Amniotic Membrane Gel Accelerates Second‐Degree Burn Wound Healing in Wister Rat

Abstract: Burn has terrible consequences for the affected patients, making them vulnerable to wound infections and septicemia, which results in physical and mental disability and death, necessitating superior treatment options. Human amniotic membrane (HAM) has been utilized in burn wounds for decades for its low immunogenicity, angiogenic, anti-inflammatory, and antimicrobial properties and for promoting epithelialization. Silver nanoparticles (AgNPs), on the other hand, have antimicrobial properties and promote fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…These studies showed that the amniotic membrane significantly contributed to the acceptance of the graft on clean wounds, serving as external protection for the skin graft. The amniotic membrane can be used as an important dressing in the treatment of infected chronic wounds after burns due to its antibacterial properties [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In our study, we also demonstrated the ability of the amniotic membrane to inhibit the growth of bacteria isolated from burn wounds, including methicillin-susceptible Staphylococcus aureus (MSSA).…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that the amniotic membrane significantly contributed to the acceptance of the graft on clean wounds, serving as external protection for the skin graft. The amniotic membrane can be used as an important dressing in the treatment of infected chronic wounds after burns due to its antibacterial properties [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In our study, we also demonstrated the ability of the amniotic membrane to inhibit the growth of bacteria isolated from burn wounds, including methicillin-susceptible Staphylococcus aureus (MSSA).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the antibacterial, anti-inflammatory, and anti-angiogenic properties of silver NPs for the treatment of burn wounds have been shown in several studies ( Pourali and Yahyaei, 2016 ; Huang et al, 2022 ; Ajaykumar et al, 2023 ). For instance, Jhumi et al (2023) have shown that the incorporation of Ag NPs into AM gels accelerates the healing of second-degree burn wounds in terms of expedited re-epithelialization and elevated contraction. It is noteworthy that in this study and many others ( Rahman et al, 2019 ; Rana et al, 2020 ; Islam et al, 2023 ; Jhumi et al, 2023 ), AM tissue has been utilized without decellularization.…”
Section: Biomedical Applications Of Am-derived Hydrogelsmentioning
confidence: 99%
“…For instance, Jhumi et al (2023) have shown that the incorporation of Ag NPs into AM gels accelerates the healing of second-degree burn wounds in terms of expedited re-epithelialization and elevated contraction. It is noteworthy that in this study and many others ( Rahman et al, 2019 ; Rana et al, 2020 ; Islam et al, 2023 ; Jhumi et al, 2023 ), AM tissue has been utilized without decellularization.…”
Section: Biomedical Applications Of Am-derived Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation